Quality assurance in preparation and installation of marine piles for the construction of coastal structures in Singapore - Khoo, Ah Kim. (2009)
The main objective of this proposed project is to seriously look into the watchwords, "Quality Assurance & Quality Control" for the preparation and installation of marine piles for coastal structure projects in Singapore. Its aim is also to develop a "practical" project quality plan based on ISO 9002 and to ensure that quality plans are effectively implemented, in order to achieve their intended purposes for the design and quality management to be fully appreciated and developed for company staff to understand the concept of "doing it right the first time", for consideration of the whole project so that we can achieve our objective of "Zero Defects in Construction".